Challenges and Opportunities of Electronic Workplace Surveillance in the Public Sector in Zimbabwe - Tongayi, Simbarashe; Ncube, Farai; Mahapa, Mildred (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
Workplace surveillance is taking the world of work by storm and is becoming the flavour of the moment as a form of scientific supervision. This study sought to unpack the challenges and opportunities of electronic workplace surveillance systems in a selected Public Sector Organisation in Zimbabwe. The study adopted qualitative research using a sample size of twenty-one participants drawn from a population of 105 employees. Primary data was collected through semi-structured questionnaires and interviews, and secondary data was gathered using company records. Findings revealed various forms of surveillance including but not limited to the use of closed-circuit television (CCTV), biometric logging, vehicle tracking, telephone tapping email, and internet monitoring. Opportunities identified centered on the possibility to increase productivity, enhancing security, curbing abuse of organizational resources, and curbing sexual harassment and bullying at the workplace. Challenges identified were the invasion of privacy, the perpetuation of power dynamics, exertion of stress, emotional labour, the killing of innovation spirit, and erosion of trust between employees and employer. The researchers recommend crafting a robust surveillance policy that clears set guidelines, and parameters and provide remedial pathways in the public sector.